Pendampingan Pemanfaatan Media Sosial atau E-Commerce dalam Upaya Pengenalan Produk dan Peningkatan Penjualan - Satyawan, Made Dudy; Triani , Ni Nyoman Alit; Yanthi, Merlyana Dwinda; Bhilawa, Loggar; Aisyahturrahmi, Aisyahturrahmi (Universitas Negeri Surabaya, 2023)
The era of digitalization affects business behavior, not only business actors whose business models change from conventional methods to the use of information technology but also the behavior of consumers who shop through social media platforms or e-commerce. Service partners who are SMEs business actors and BUMDes management bodies in villages in Bojonegoro Regency, East Java, have problems introducing their businesses and products or services. Conventional methods sacrifice marketing costs that are not small and have the potential to fail, as well as the capital spent on shop rentals. The increasing number of mobile and internet users in Indonesia is an opportunity to expand the market and marketing of products or services owned by service partners. Utilization of Social Media or E-Commerce is an effort to introduce products and increase sales of partner businesses. The service implementation methods include the creation of a product catalog, selection, and training on the use of social media or e-commerce